Access to Justice for Persons with Mental Disabilities as Victims of Sexual Violence: A Case Study of Palangka Raya - Jeni Yestari; Suriansyah Murhaini; Claudia Yuni Pramita; Rizki Setyobowo Sangalang (Universitas Muhammadiyah Surabaya, 2026)
Sexual violence against persons with mental disorders (ODGJ) raises serious legal issues related to the fulfillment of victims' rights and access to justice, particularly due to the victims’ limited capacity to provide testimony and defend themselves in criminal proceedings. This study aims to analyze the forms of legal protection and the effectiveness of regulatory implementation in handling ODGJ as victims of sexual violence in Palangka Raya City. This research employs an empirical legal research method through field data collection and analysis of relevant legal frameworks. The findings indicate that although Law No. 12 of 2022 concerning Sexual Violence Crimes and Law No. 17 of 2023 concerning Health provide a normative basis for victim protection, their implementation remains limited in practice. In Palangka Raya, several specific obstacles were identified, including the absence of specialized psychological assessment mechanisms to support victim testimony, limited availability of mental health experts during the investigation process, and the lack of standardized procedures for adapting examination techniques to victims with mental disabilities. In addition, the absence of integrated service facilities and limited training for law enforcement officers regarding disability-sensitive approaches further complicate the handling of such cases. This study emphasizes that legal protection for ODGJ victims of sexual violence requires a more comprehensive approach through capacity building for law enforcement officials, adaptive evidentiary mechanisms, and stronger institutional coordination to ensure the effective fulfillment of victims’ rights.